Semiosis and the Culture of Rupture - Art Leete (Journal of Ethnology and Folkloristics)
Overview about the 7th Semiosis and Culture Conference organised in May 2010 by the Komi State Pedagogical Institute in Syktyvkar, Republic of Komi, Russia.